Effectiveness of Basic Physics Practicum in Determining Gravity Acceleration Based on Virtual Mobile Observatory - Ma'ruf Ma'ruf; Ana Dhiqfaini Sultan (Kasuari: Physics Education Journal (KPEJ), 2021)
This study aims to analyze the effectiveness of the basic physics practicum trial for determining Earth's gravity based on a virtual mobile observatory, and to measure the ICT literacy skills of prospective physics teacher students. This study uses a quantitative descriptive method. The sample data for this study were first semester students, totaling 13 people who were in one class at the Physics Education Department, Universitas Muhammadiyah Makassar for the academic year even semester 2020-2021. The location of the research was carried out in the basic physics laboratory. The instrument used was an observation sheet on the implementation of physics practicum and a test of ICT literacy skills for prospective physics teacher students. Based on the results of the research and discussion, it can be concluded that the effectiveness of the results of the basic physics practicum experiment to determine Earth's gravity based on a virtual mobile observatory is in the very good category, and the results of the ICT literacy skills of prospective physics teacher students are in the good category. The implication of this research is that it is very suitable for the Covid-19 pandemic period as an online practicum.